THE INFLUENCE OF BRANDS AND ADVERTISEMENTS ON THE PURCHASING INTEREST OF FEMALE STUDENTS TOWARDS EMINA COSMETIC PRODUCTS AT STIA AMUNTAI - Nisa, Murdiatun; Fadillah, Haris (PPPM STIA Amuntai, 2025)
The study aims to determine the influence of brands and advertisements on the purchasing interest of female students towards Emina cosmetic products at STIA Amuntai. The background of this study is the rapid growth of the cosmetics industry in Indonesia, especially among teenagers and female students, who are the main targets of Emina products. This study uses a quantitative approach using a survey method. Then the data were collected using questionnaires distributed to 94 female students of STIA Amuntai as active respondents who use Emina products. The analysis technique used is multiple linear regression using SPSS software version 27. The results of the analysis state that simultaneously, brand and advertising variables have a significant influence on purchasing interest, a significant value of 0.000 (F table 3.097). However, partially, only the advertising variable has a significant influence, the calculated t value of 9.068> T Table 1.986 and a significance value of 0.000 <0.05. This finding indicates that in the context of Emina cosmetic sales among female students, advertising has a much more dominant role than brands in influencing purchasing interest. Therefore, companies are advised to continually update their advertising tactics to be more innovative and tailored to the characteristics of the younger generation.